1 Corinthians 1:18-31 from a rhetorical perspective - A. H. Snyman (Acta Theologica)
The approach followed in this article differs from that of researchers who force ancient rhetorical categories on a text or who regard only a few stylistic devices as rhetorical. The analysis is done in terms of what is called a “grounded theoretical approach.” This approach is briefly summarised, followed by a description of the rhetorical status of the letter and a systematic analysis of 1 Corinthians 1:18-31. It is argued that these fourteen verses form an integral part of Paul’s rhetorical strategy (constructed from the text itself) and aimed at persuading the Corinthians to accept his explanation of the gospel. The article concludes that a text-centered approach, with its focus on the functional aspects of the text, provides a better alternative to existing approaches, that focus on the formal aspects of the text.